Banking on Milk An Ethnography of Donor Human Milk Relations - Cassidy, Tanya (Taylor & Francis, 2019)
Banking on Milk takes the reader on a journey through the everyday life of donor human milk banking across the United Kingdom (UK) and beyond, asking questions such as the following: Why do people decide to donate? How do parents of recipients hear about human milk? How does milk donation impact on lifestyle choices? Chapters record the practical everyday reality of work in a milk bank by drawing on extensive ethnographic observations and sensitive interview data from donors, mothers of recipients and the staff of four different milk banks from across the UK, and visits to milk banks across Europe and North America. It discusses the ongoing pressures to do with supply, demand and distribution. An empirically informed ""ethnography of the contemporary"", where both biosociality and biopower abound, this book includes an exploration of how milk banks evolved from registering wet nurses with hospitals, showing how a regulatory culture of medical authority began to quantify and organize human milk as a commodity. This book is a valuable read for all those with an interest in breastfeeding or organ and tissue donation from a range of fields, including midwifery, sociology, anthropology, geography, cultural studies and public health.